Foresight for Science, Technology and Innovation - Miles, Ian.; Saritas, Ozcan; Sokolov, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
Decision-makers at all levels are being confronted with novel complexities and uncertainties and face long-term challenges which require foresight about long-term future prospects, assumptions, and strategies. This book explores how foresight studies can be systematically undertaken and used in this context. It explicates why and how methods like horizon scanning, scenario planning, and roadmapping should be applied when dealing with high levels of uncertainty. The scope of the book moves beyond "narrow" technology foresight, towards addressing systemic interrelations between social, technological, economic, environmental, and political systems. Applications of foresight tools to such fields as energy, cities, health, transportation, education, and sustainability are considered as well as enabling technologies including nano-, bio-, and information technologies and cognitive sciences. The approaches will be illustrated with specific actual cases.
1 Introduction -- 2 Foresight for STI - What and Why -- 3 Initiation-Scoping and Managing ForSTI -- 4 Interaction - Participation and Recruitment -- 5 Intelligence - Environmental and Horizon Scanning -- 6 Intelligence - Delphi -- 7 Imagination - Scenarios and Alternative Futures -- 8 Integration - Modelling -- 9 From Integration to Interpretation - Translating ForSTI into Strategies -- 10 Intervention and Impact - Outcomes, Action and Evaluation -- 11 Conclusion. .
Keywords: Economic policy; Public administration; R & D/Technology Policy; Innovation/Technology Management; Operations Research/Decision Theory.market